Kajian Kritis al-Ṣaifī wa al-Syitāʾī dalam ʿUlūm al-Qurʾān - Nur Fiatin Hafidh (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2021)
al-Ṣaifī and al-Syitā’ī are two unexplored topics in the discourses of the Qur’anic chronology. While being so, such categorization that is based on a seasonal division of the Arabic peninsula is confusing given the subtropical nature of the region. This study aims to identify a further classification of al-Ṣaifī and al-Syitā’ī, by analysing their characteristics as well as their congruity with the revelation time. This study reveals three findings: First, in the ʿUlūm al-Qurʾān books, the spring and the autumn are not considered important for they are only change phases into the summer and winter. Second, the further classification resulted 129 summer verses and 19 winter verses. Third, the characteristic of ṣaifī much told about one’s buffetings, while syitāī is identic with sadness. Thus, ṣaifī presents as media of faith consolidation by using causality model in His verses and syitāī is to remove the sadness through the good news in the verse content.